Persepsi Kelompok Pemandu Wisata Terhadap Konservasi Penyu di Pesisir Pulau Bunaken, Taman Nasional Bunaken, Manado, Sulawesi Utara - Rumbay, Julia Angel; Koneri, Roni; Langoy, Marnix; Handoyo, Eko; Wijaya, Pandu (Sam Ratulangi University, 2022)
Public perception of turtle conservation in an area will determine the success of turtle conservation activities. This study aims to analyze the perception of tour guide groups towards turtle conservation on the coast of Bunaken Island, Bunaken National Park, Manado, North Sulawesi. The research method was carried out by means of observation and surveys. Collecting data in the form of interviews with a questionnaire guide. The selection of respondents was carried out by purposive sampling with the target group of tour guides, especially dive guides. Data analysis was carried out using a qualitative descriptive method. The results showed that most of the respondents (78%) already understand about turtle conservation and no longer consume turtles (100%). The turtle habitat which includes coral reefs and seagrasses still supports the presence of turtles and turtles are almost visible at all observation locations. The understanding of turtle conservation by dive guides is quite good, but to maintain the sustainability of conservation so that it is maximized, it is necessary to provide guidance and supervision to the diving guides and also to the surrounding community.